Analisis Kapasitas Parking Stand dan Pengembangan Apron Bandar Udara Sentani – Jayapura - David Wenda; Efendy Tambunan; Risma M. Simanjuntak (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Sentani Jayapura Airport is one of the airports in Papua Province and is the busiest airport serving domestic routes in Indonesia. Papua Province is experiencing growth and equitable growth. In 2018 the growth of 64,698 aircraft movements took off and landed every day. An average of 120 flights per day. In 2018 the movement growth of 64,698 aircraft took off and landed every day. An average of 120 flights per day. The method used for motion prediction is the linear trend method, using data information for the last 5 years (2015-2019) obtained by PT Angkasa Pura I Sentani Branch. The method used the Pignataro method to obtain the peak hour rate pattern for the current year, then use it to determine the number of aircraft movements for the planned year by multiplying the rate pattern obtained by the number of annual aircraft movements generated by the forecast. The capacity of the Sentani Papua Airport Apron is 38 parking stands but in operation it is only used as many as 27 parking stands consisting of large and small body aircraft. The number of parking stands needed for the next 10 years (2029) is 21 parking stands for the category of large-bodied aircraft types (narrow body). The results showed that for the next 10 years (2029) the capacity required geometric development / expansion of the apron with a length of 936 m and a width of 136 m